Fluorescence lifetime microscopy unveils the supramolecular organization of liposomal Doxorubicin. Issue 25 (17th June 2022) - Tentori, Paolo; Signore, Giovanni; Camposeo, Andrea; Carretta, Annalisa; Ferri, Gianmarco; Pingue, Pasqualantonio; Luin, Stefano; Pozzi, Daniela; Gratton, Enrico; Beltram, Fabio; Caracciolo, Giulio; Cardarelli, Francesco
Abstract : The supramolecular organization of Doxorubicin (DOX) within the standard Doxoves® liposomal formulation (DOX®) is investigated using visible light and phasor approach to fluorescence lifetime imaging (phasor-FLIM). Abstract : The supramolecular organization of Doxorubicin (DOX) within the standard Doxoves® liposomal formulation (DOX®) is investigated using visible light and phasor approach to fluorescence lifetime imaging (phasor-FLIM). First, the phasor-FLIM signature of DOX® is resolved into the contribution of three co-existing fluorescent species, each with its characteristic mono-exponential lifetime, namely: crystallized DOX (DOXc, 0.2 ns), free DOX (DOXf, 1.0 ns), and DOX bound to the liposomal membrane (DOXb, 4.5 ns). Then, the exact molar fractions of the three species are determined by combining phasor-FLIM with quantitative absorption/fluorescence spectroscopy on DOXc, DOXf, and DOXb pure standards. The final picture on DOX® comprises most of the drug in the crystallized form (∼98%), with the remaining fractions divided between free (∼1.4%) and membrane-bound drug (∼0.7%). Finally, phasor-FLIM in the presence of a DOX dynamic quencher allows us to suggest that DOXf is both encapsulated and non-encapsulated, and that DOXb is present on both liposome-membrane leaflets. We argue that the present experimental protocol can be applied to the investigation of the supramolecular organization of encapsulated luminescent drugs/molecules all the way from the production phase to their state within living matter.